Healing the Wounded Giant : Maintaining Military Preeminence while Cutting the Defense Budget - O'Hanlon, Michael E. (Book collections on Project MUSE., 2013)
President Barack Obama survived a tenuous economy and a toxic political environment to win re-election in 2012, but the bitter partisan divide in Washington survived as well. So did the country's huge fiscal deficit. in this, the latest in a long line of Brookings Institution analyses of the defense budget, Michael O'Hanlon considers how best to balance national security and fiscal responsibility during a period of prolonged economic stress and political acrimony --even as the world remains unsettled, from Afghanistan to Iran to Syria to the western Pacific region. O'Hanlon explains why the large defense cuts that would result from prolonged sequestration or from deficit-reduction projects such as the Bowles-Simpson plan are too deep. But the bulk of his book represents an effort to look for greater savings than the Obama administration's 2012 proposals would allow.